2011
DOI: 10.3111/13696998.2011.576295
|View full text |Cite
|
Sign up to set email alerts
|

Incremental third-party costs associated with COPD exacerbations: a retrospective claims analysis

Abstract: Exacerbations, especially severe ones, result in a significant economic burden for third-party payers. Effective management of COPD and prevention of exacerbations may lead to improved patient outcomes and reduction in total healthcare costs for long-term management of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 26 publications
5
31
0
Order By: Relevance
“…A history of E-COPD therefore suggests a future frequent exacerbator phenotype, which leads to higher healthcare costs and use, as recent US studies have reported. [10], [12], [28] Furthermore, the healthcare costs increased in proportion to the severity of E-COPD, since a severe exacerbation requires hospitalization, at an average cost in our study of 3985 €, which is consistent with previous data. [29].…”
Section: Discussionsupporting
confidence: 92%
“…A history of E-COPD therefore suggests a future frequent exacerbator phenotype, which leads to higher healthcare costs and use, as recent US studies have reported. [10], [12], [28] Furthermore, the healthcare costs increased in proportion to the severity of E-COPD, since a severe exacerbation requires hospitalization, at an average cost in our study of 3985 €, which is consistent with previous data. [29].…”
Section: Discussionsupporting
confidence: 92%
“…COPD patients using multiple long-acting maintenance inhalers (two or more prescriptions) have also been shown to be less adherent and have higher discontinuation rates than single-inhaler users [7]. Improving compliance among this patient population is particularly important, as poor adherence to drug therapy has been identified as the major factor resulting in emergency hospitalization among COPD patients [810].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the current study findings should be interpreted with appropriate caution. COPD exacerbations are clinically meaningful events [4] with significant healthcare costs [24][25][26]. Considered the ''stroke of the lungs,'' COPD exacerbations initiate a catastrophic cascade of increased symptoms, decline in lung function, reduced exercise/physical function, increased hospitalization risk, lower quality of life, and accelerated disease progression [27].…”
Section: Discussionmentioning
confidence: 99%